2020
DOI: 10.1101/2020.08.14.20172429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Practice and associated factors towards the Prevention of COVID-19 among high-risk groups: A cross-sectional study in Addis Ababa, Ethiopia

Abstract: Background Coronavirus disease-19 is a highly transmittable virus that continues to disrupt livelihoods, particularly those of low-income segments of society, around the world. In Ethiopia, more specifically in the capital city of Addis Ababa, a sudden increase in the number of confirmed positive cases in high risk groups of the community has been observed over the last few weeks of the first case. Therefore, this study aims to assess knowledge, practices and associated factors that can contribute to the preve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
5
16
0
Order By: Relevance
“…This is comparable with the finding from Addis Ababa city where 85% and 83% mentioned hand washing and social distancing as a COVID-19 prevention measures, respectively. 7 Another online survey conducted in Ethiopia also documented a 90% prevention knowledge of maintaining social distance and frequent hand washing, which is in line with our finding. 14 Avoiding handshaking is the third most popular prevention method cited by participants (54.7%), followed by staying at home (44.6%).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is comparable with the finding from Addis Ababa city where 85% and 83% mentioned hand washing and social distancing as a COVID-19 prevention measures, respectively. 7 Another online survey conducted in Ethiopia also documented a 90% prevention knowledge of maintaining social distance and frequent hand washing, which is in line with our finding. 14 Avoiding handshaking is the third most popular prevention method cited by participants (54.7%), followed by staying at home (44.6%).…”
Section: Discussionsupporting
confidence: 89%
“…This result shows that participant’s knowledge on COVID-19 is far broader than any time previously. 7–11 and shows that coronavirus risk communication and awareness creation campaign across the country have made a positive impact on the public knowledge of the disease. This finding is much higher than other studies in the northern part of the country those reported 42.9% and 60.7% knowledgeable participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teens and young adults are ignorant of COVID-19 preventive measures for a variety of reasons, including underestimating the risk, believing they are not at risk and a lack of accountability. 46 The finding is in line with other studies conducted in Ethiopia, 30 , 47 and India. 48 …”
Section: Discussionsupporting
confidence: 83%
“…The preventive practice was measured using 10 items of questions and those who respond as yes were given 1 point while no was marked as 0. The total prevention practice score ranges from 0–10 and a score with a cut-off ≥ 8 (80%) was considered as good practice while <8 was taken as a poor practice [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%